The effect of vitamin D administration on biochemical factors in polycystic ovary syndrome patients: a randomized controlled clinical trial study - solmaz sedghi; Fariba Almassi Nokiani; Maliheh Fakehi; Kobra Tahermanesh; Peyman Akbari (Mashhad University of Medical Sciences, 2024)
Introduction: Despite the effect of vitamin D in improving clinical and laboratory symptoms and insulin resistance and hyperandrogenism, there are still doubts about the role of vitamin D in the treatment of PCOS. Therefore, the present study was conducted with aim to investigate the effect of vitamin D on biochemical indices and sexual hormones in PCOS patients.Methods: This clinical trial study was conducted in 2023 on 213 women aged 18-40 with PCOS diagnosis and vitamin D deficiency in Shahid Akbarabadi Hospital. Patients with a serum level greater than or equal to 30 ng/ml of vitamin D were included in the study and were divided into control and intervention groups. The control group was prescribed metformin 500 mg daily and the intervention group metformin 500 mg daily plus vitamin D 50,000 units weekly for 12 weeks and then the above factors were again checked. Data analysis was done using SPSS statistical software (version 22) and Mann-Whitney and Chi-square tests. P<0.05 was considered statistically significant.Results: : The mean of FSH, TG, HDL, and vitamin D factors after the intervention significantly increased compared to before the intervention (p<0.05). However, the mean of FBS and HOMA IR factors reduced after the intervention compared to before the intervention, and a statistically significant relationship was observed (p<0.05).Conclusion: The use of vitamin D in PCOS patients can have an effect on laboratory indices such as FBS, HOMA IR, FSH, TG and HDL.